2021
DOI: 10.1038/s41598-021-83665-4
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of myocardial infarction and stroke in head and neck cancer patients

Abstract: Various treatment modalities are used for head and neck cancer (HNC). This study analyzed the incidence and risks of myocardial infarction (MI) and stroke by cancer site and treatment modality in 22,737 patients newly diagnosed with HNC registered in the Korean National Health Insurance Service database in 2007–2013. An additional 68,211 patients without HNC, stroke, or MI were identified as the control group. The risks for MI (hazard ratio [HR] = 1.38, 95% confidence interval [CI] 1.24–1.53), stroke (HR = 1.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 45 publications
0
28
2
Order By: Relevance
“…Out of 22 studies that reported the combined incidence of ischemic and hemorrhagic stroke at 1 year, eight were cohort studies that included multiple types of cancer ( Supplementary Figure 3 ) ( 12 , 14 , 15 , 25 , 27 , 31 , 33 , 34 ). The remaining 14 studies were limited to specific cancer subtypes including head and neck cancer ( n = 3) ( 16 , 24 , 28 ), hematologic malignancies ( n = 2) ( 19 , 29 ), breast cancer ( n = 2) ( 21 , 23 ), and thyroid cancer ( n = 2) ( 26 , 32 ). There was only one study for each of the following subtypes of cancer: pancreatic, cervical, prostate, colorectal, and hepatic ( 17 , 18 , 20 , 22 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 22 studies that reported the combined incidence of ischemic and hemorrhagic stroke at 1 year, eight were cohort studies that included multiple types of cancer ( Supplementary Figure 3 ) ( 12 , 14 , 15 , 25 , 27 , 31 , 33 , 34 ). The remaining 14 studies were limited to specific cancer subtypes including head and neck cancer ( n = 3) ( 16 , 24 , 28 ), hematologic malignancies ( n = 2) ( 19 , 29 ), breast cancer ( n = 2) ( 21 , 23 ), and thyroid cancer ( n = 2) ( 26 , 32 ). There was only one study for each of the following subtypes of cancer: pancreatic, cervical, prostate, colorectal, and hepatic ( 17 , 18 , 20 , 22 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using the NOS risk of bias tool, we found that 6/41 studies were “poor quality,” one was “fair quality,” and the remaining 34 were “good quality” ( Supplementary Table 2 ). Subgroup analysis stratified by the ROB ratings found that 20 of 22 studies that reported 1-year stroke outcomes were deemed “good quality” ( 12 , 14 28 , 30 33 ), while one received a “poor” rating ( 34 ) and one received a “fair” rating ( 29 ). The studies that received a “good” rating had a similar pooled incidence of stroke at 1 year compared to the primary analysis ( Supplementary Figure 6 ): 1.4% (95% CI 0.9–2.2%, I 2 = 99.92%).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported increased risks of CVD or stroke after the diagnosis of HNCA 9‐13 . Kwon et al 12 reported a 1.376‐fold higher incidence of myocardial infarction (MI) and 1.483‐fold higher incidence of stroke in the Korean population compared to the control group. In the Taiwanese population, the risk of stroke incidence was 1.44‐fold higher than that in the control cohort 13 .…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In this report, CVD and stroke occurred in 6.4% and 5.2% of the HNCA population, respectively, rates similar to those reported previously. 12,13 Likewise, the risk factors associated with increased risk were male sex, older age, and related comorbidities, such as HTN or DM. [11][12][13] Among these related comorbidities, HTN, DM, and hyperlipidemia are also traditional risk factors for CVD or stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of CVD was reported to be inconsistent among cancers [ 4 , 5 ]. However, previous retrospective cohort studies have shown conflicting results: patients with cancer had a higher [ 6 ] or lower [ 7 ] risk of CVD than patients without cancers, men had a higher [ 6 ] or similar [ 8 ] risk as that of women, younger cancer patients had a higher [ 9 ] or lower [ 6 ] risk of CVD than the elderly, and the risk of CVD decreased [ 10 ] or increased [ 11 ] gradually after the diagnosis of cancer.…”
Section: Introductionmentioning
confidence: 99%